Delivery in Pregnant Women Infected With SARS-Co-2: A Fast Review. Issue 1 (24th March 2021) - Parazzini, F.; Bortolus, R.; Mauri, P.A.; Favilli, A.; Gerli, S.; Ferrazzi, E.
Abstract : ( Int J Gynecol Obstet . 2020;150:41–46) There is still much to be learned about the effects of coronavirus disease 2019 (COVID-19) on pregnant women. The risk of transmission of the virus to the fetus is still unclear. There are now some published case reports and clinical series on pregnancies and deliveries in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This study aimed to review the current evidence concerning mode of delivery, immediate neonatal outcomes, and vertical or peripartum transmission in pregnant patients with confirmed SARS-CoV-2 infection.